Arbuscular mycorrhizal fungi enhance phosphate uptake and alter bacterial communities in maize rhizosphere soil - Lu, Yufan; Yan, Yixiu; Qin, Jie; Ou, Luyan; Yang, Xinyu; Liu, Fang; Xu, Yunjian (Frontiers in Plant Science, 2023)
Arbuscular mycorrhizal fungi (AMF) can symbiosis with many plants and improve nutrient uptake for their host plant. The rhizosphere microorganisms have been pointed to play important roles in helping AMF to mobilize soil insoluble nutrients, especially phosphorus. Whether the change in phosphate transport under AMF colonization will affect rhizosphere microorganisms is still unknown. Here, we evaluated the links of interactions among AMF and the rhizosphere bacterial community of maize (Zea mays L.) by using a maize mycorrhizal defective mutant. Loss of mycorrhizal symbiosis function reduced the phosphorus concentration, biomass, and shoot length of maize colonized by AMF. Using 16S rRNA gene amplicon high-throughput sequencing, we found that the mutant material shifted the bacterial community in the rhizosphere under AMF colonization. Further functional prediction based on amplicon sequencing indicated that rhizosphere bacteria involved in sulfur reduction were recruited by the AMF colonized mutant, but reduced in AMF colonized wild-type. These bacteria harbored much abundance of sulfur metabolism-related genes and negatively correlated with biomass and phosphorus concentrations of maize. Collectively, this study shows that AMF symbiosis recruited rhizosphere bacterial communities to improve soil phosphate mobilization, which may also play a potential role in regulating sulfur uptake. This study provides a theoretical basis for improving crop adaptation to nutrient deficiency through soil microbial management practices.